POME Dye Removal Performance during Pervaporation using Lignin Nanoparticle Integrated into Polyamide Thin Film Composite Membranes - Riani Ayu Lestari; Rabiatul Wahdah; Muthia Elma; Primata Mardina; Desi Nurandini; Iryanti Fatyasari Nata (Politeknik Negeri Malang, 2026)
Palm oil mill effluent (POME) contains recalcitrant, dye-like chromophoric compounds that are difficult to remove using conventional treatment, leading to persistent colour pollution and limiting safe discharge or reuse. Although polyamide thin-film composite (PA-TFC) membranes offer strong selectivity, their performance in high-strength wastewater is often constrained by the permeability-selectivity trade-off and susceptibility to fouling. To address this gap, this study investigates a bio-based modification strategy by integrating lignosulfonate-derived lignin particles into the polyamide selective layer to enhance pervaporation-based decolorization. Lignin-modified PA-TFC membranes were fabricated via interfacial polymerization with molar ratio MPD: TMC for 0.00925:0.0188 and 0.25% of lignosulfonate. It was then evaluated for pervaporation flux, colour rejection, and chemical stability during POME treatment. Chemical and structural characterization by FTIR indicated changes in surface functional groups consistent with enhanced intermolecular interactions between lignin and the polyamide matrix. The lignin-integrated membrane achieved an improved separation performance, reaching a flux of 17 ± 0.8 kg.m-2.h-1 with up to 85% colour rejection, outperforming the pristine polyamide membrane. The performance enhancement is attributed to improved hydrophilicity and a more favourable selective-layer microstructure enabled by the homogeneous distribution of lignin particles and hydrogen-bonding interactions within the polyamide network. Overall, incorporating lignin as a renewable additive provides a promising route to develop higher-performance PA-TFC membranes for pervaporation treatment of POME, supporting more sustainable industrial wastewater management and reducing colour-related environmental impacts.